Assessment of patients’ self-perceived intensive care unit discomforts: Validation of the 18-item version of the IPREA - Karine Baumstarck; Mohamed Boucekine; Philippe Estagnasie; Marie-Agnès Geantot; Audrey Berric; Georges Simon; Bernard Floccard; Thomas Signouret; Mélanie Fromentin; Martine Nyunga; Achille Sossou; Marion Venot; et al. (Health and Quality of Life Outcomes, 2019)
Abstract Background and aims We reported the validation of the 18-item version of the ‘Inconforts des Patients de REAnimation (IPREA)’ questionnaire that includes 2 new items exploring feeling depressed and shortness of breath during an intensive care unit (ICU) stay. Methods The validation process was integrated in a multicenter, cluster-randomized, controlled, two-parallel group study built to assess the effectiveness of a tailored multicomponent program for reducing self-perceived discomfort in the ICU. All patients aged 18 years or older who survived an ICU stay of 3 calendar days or more were eligible for inclusion. Data collection included demographics (sex, age), type of admission (medical and surgical), health status scores at admission (Knaus score and McCabe index, Simplified Acute Physiology Score (SAPS) II), specific ICU therapeutics such as mechanical ventilation (MV), noninvasive ventilation (NIV), use of vasopressors, or renal replacement therapy (RRT), and ICU stay duration. Results A total of 994 patients were included. The initial structure of IPREA was confirmed using confirmatory factor analysis showing satisfactory fit (RMSEA at 0.042, CFI at 0.912). No multidimensional structure was identified, allowing the calculation of an overall discomfort score. The three highest discomforts were sleep deprivation, thirst, and perfusion lines and other devices, and the 3 lowest discomforts were limited visiting hours, hunger, and isolation. The overall discomfort score of the 18-item version of IPREA did not differ between men and women. Higher age was significantly correlated with a lower overall discomfort score. While MV was not linked to self-reported discomfort, patients treated by NIV reported higher overall discomfort scores than patients not treated by NIV. Conclusion The 18-item version of IPREA is easy to use and possesses satisfactory psychometric properties. The availability of a reliable and valid French questionnaire asking about patients’ self-perceived ICU discomforts enables feedback from the health care team to be incorporated in a continuous quality health care improvement strategy. Trial registration clinicaltrial.gov NCT02442934 (registration date: May 18, 2015, retrospectively registered).